THE STUDY OF HEMATOLOGICAL AND FUNCTIONAL INDICATORS IN STUDENTS DURING THE EXAMINATION SESSION (Journal of Educational Sciences, 2018)
The article considers the changes in hematological and functional indicators in students during theexamination session. To assess the possible occurrence of violations of students ‘health status, ascertainingthe level of the price of adaptation when influencing the students’ body of university loads, the mostinformative indicators are determined. In terms of leukocyte status, 45% of students who have leukocytecounts within the reference values of the norm have a successful adaptation reaction corresponding totheir health. When comparing hematological indicators and health indicators, the most unfavorablevalues were found in the form of elevated glucose, increased systolic pressure, and an increase in lymphocytecount. An increase in the lymphocyte count is considered as one of the indicators of unfavorableadaptation to higher education. At 33%, the average level of stress was found, 67% showed a low levelof stress, which indicates a state of psychological adaptation to workloads. Adaptation of students tostudy conditions in higher education is a complex multi-level physiological process. The development ofdisadaptation during the training period can have a negative impact on the functional state of the organismand lead to the development of pathological processes.Key words: study load, students, lymphocyte, monocyte, adaptation.